PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI HOTEL ROYAL KUNINGAN - Yesi Yasinta; Aris Budiono (Human Capital Development, 2017)
Purpose- The purpose of this analysis is to know about an effect of the leadership and motivation affect simultaneously or partially of employee performance. Design/methodology/approach- The population of this analysis is the areemployeeatHotel Royal Kuningan. With the sample used in this research were the employee as much as 100 people. The technique sampling which used is multiple linear regression, validity test, reliability test, classic assumption test (normality test, multicollinearity test, heterokedasticity test, and linearity test) while the best or hypothesis includes F test, T test, partial analysis test and coefficient of determination (r2). Findings- The analysis that can know from the influence of leadership and motivationwhich effected the employee performanceatHotel Royal Kuningan, either partially or simultaneously